The effect of non-adherence to antipsychotic treatment on rehospitalization in patients with psychotic disorders - H. Abdullah-Koolmees; S. Nawzad; T.C.G. Egberts; J. Vuyk; H. Gardarsdottir; E.R. Heerdink (SAGE Publishing, 2021)
Background and Aims: Many patients with psychotic disorders are non-adherent to antipsychotic (AP) medication(s), potentially contributing to rehospitalization. It is unknown whether non-adherence in different phases of AP use is associated with rehospitalization. The aim of this study was to assess the association between non-adherence to APs and rehospitalization in patients with psychotic disorders. Non-adherence was assessed specifically for the initiation, continued drug use and early discontinuation of AP use. Methods: A retrospective follow-up study was performed. Adult patients were included at discharge if they suffered from schizophrenia, psychotic, or bipolar I disorder; had been hospitalized in a psychiatric hospital for ⩾7 days; and were treated with oral APs. Patients discharged between January 2006 and December 2009 from Altrecht Mental Health Care were included. Non-adherence was studied in the three phases of medication use: initiation, continued drug use (implementation) and (early) discontinuation after discharge until the end of follow up or until patients were rehospitalized. Cox regression analysis was used to assess the strength of the association between non-adherence for the different phases of AP use and rehospitalization during follow up and expressed as relative risk (RR) with 95% confidence intervals (CI). Results: A total of 417 patients were included. Patients who did not initiate their APs compared with those who did in the first month (RR = 1.62, 95% CI: 1.19-2.19) and between the first and third month after discharge (RR = 1.70, 95% CI: 1.04-2.79) had the highest risk for rehospitalization during follow up. Overall, patients who did not initiate their AP medication within the first year after discharge had a RR of 2.70 (95% CI: 1.97-3.68) for rehospitalization during follow up compared with those that initiated their AP. Conclusion: Not initiating APs right after discharge was associated with an increased risk of rehospitalization. Interventions should aim to promote the initiation of APs soon after discharge to minimize the risk of rehospitalization.